Hepatic FTO is dispensable for the regulation of metabolism but counteracts HCC development in vivo - Melanie J. Mittenbühler; Katarzyna Saedler; Hendrik Nolte; Lara Kern; Jun Zhou; Shu-Bing Qian; Lydia Meder; Roland T. Ullrich; Jens C. Brüning; F. Thomas Wunderlich (Elsevier, 2020)
Objective: Single-nucleotide polymorphisms in the FTO gene encoding an m6Am and an m6A demethylase are associated with obesity. Moreover, recent studies have linked a dysregulation of m6A modifications and its machinery, including FTO, to the development of several forms of cancers. However, the functional role of hepatic FTO in metabolism and the development and progression of hepatocellular carcinoma (HCC), a proteotypic obesity-associated cancer, remains unclear. Thus, we aimed to reveal the role of hepatic FTO in metabolism and in the initiation and progression of HCC in vivo. Methods: We generated mice with hepatic FTO deficiency (FTOL−KO). The effect of hepatic FTO on metabolism was investigated by extensive metabolic phenotyping. To determine the impact of hepatic FTO on HCC development, FTOL−KO and Ctrl mice were subjected to long-term diethylnitrosamine (DEN)-induced HCC-development and the tumor initiation phase was examined via a short-term DEN protocol. Results: In long-term DEN experiments, FTOL−KO mice exhibit increased HCC burden compared to Ctrl mice. In the tumor initiation phase, Ctrl mice display a dynamic regulation of FTO upon induction of liver damage, while this response is abrogated in FTO-deficient mice. Proteomic analyses revealed that liver damage-induced increases in FTO expression reduce CUL4A protein abundance. Functionally, simultaneous knockdown of Cul4a reverses the increased hepatocyte proliferation observed upon loss of FTO. Conclusion: Collectively, our study demonstrates that hepatic FTO is dispensable for the control of energy homeostasis and glucose metabolism. However, we show a protective function of FTO in liver carcinogenesis and suggest the FTO-dependent dynamic mRNA demethylation of Cul4a in the initiation of HCC development contributes to this effect.